Developing fibrillated cellulose as a sustainable technological material - Li, Tian; Chen, Chaoji; Brozena, Alexandra H.; Zhu, J. Y.; Xu, Lixian; Driemeier, Carlos; Dai, Jiaqi; Rojas, Orlando J.; Isogai, Akira; Wågberg, Lars; Hu, Liangbing (Nature (London), 2021)
Cellulose is the most abundant biopolymer on Earth, found in trees, waste from agricultural crops and other biomass. The fibres that comprise cellulose can be broken down into building blocks, known as fibrillated cellulose, of varying, controllable dimensions that extend to the nanoscale. Fibrillated cellulose is harvested from renewable resources, so its sustainability potential combined with its other functional properties (mechanical, optical, thermal and fluidic, for example) gives this nanomaterial unique technological appeal. Here we explore the use of fibrillated cellulose in the fabrication of materials ranging from composites and macrofibres, to thin films, porous membranes and gels. We discuss research directions for the practical exploitation of these structures and the remaining challenges to overcome before fibrillated cellulose materials can reach their full potential. Finally, we highlight some key issues towards successful manufacturing scale-up of this family of materials. Opportunities for the application of fibrillated cellulose materials—which can be extracted from renewable resources—and broader manufacturing issues of scale-up, sustainability and synergy with the paper-making industry are discussed.